Effectiveness of lifestyle interventions for preventing harmful weight gain among young adults from lower socioeconomic status and ethnically diverse backgrounds: a systematic review. (26th November 2017) - Hayba, N.; Partridge, S. R.; Nour, M. M.; Grech, A.; Allman Farinelli, M.
Summary: The incidence of overweight and obesity are increasing with each successive generation of young adults. Associated co‐morbidities will emerge at an earlier age unless weight gain is prevented. Evidence has demonstrated young adults (aged 18–35 years) from low socioeconomic and ethnically diverse backgrounds are at greater risk of overweight or obesity, yet it is unclear how to effectively intervene in this population. This systematic review aimed to assess the effectiveness of lifestyle interventions conducted in this population. Thirty studies reporting on lifestyle interventions for prevention of weight gain were identified from eight electronic databases searched. Six interventions included subgroup analyses to determine if ethnicity moderated weight change, and two included subgroup analyses to determine if socioeconomic status had an effect on change in weight. Five of these six studies were effective in preventing weight gain, and subgroup analyses showed no differences in effect by ethnicity. Of these five studies, two included a subgroup analysis that showed socioeconomic status to have no effect on weight outcome. Despite the promising results from these five lifestyle interventions utilizing online and mobile components to effectively reach and prevent weight gain in this priority population, the evidence base of high quality trials is limited.